An analytical approach and finite element evaluation of leakage fluxes of the PMs in a non-slotted axial flux permanent magnet machine. Issue 3 (8th May 2018) - Mirzahosseini, Reza; Darabi, Ahmad; Assili, Mohsen
Abstract : Purpose: Consideration of leakage fluxes in the preliminary design stage of a machine is important for accurate determination of machine dimensions and prediction of performance characteristics. This paper aims to obtain some equations for calculating the average air gap flux density, the flux density within the magnet and the air gap leakage flux factor. Design/methodology/approach: A detailed magnetic equivalent circuit (MEC) is presented for a TORUS-type non-slotted axial flux permanent magnet (TORUS-NS AFPM) machine. In this MEC, the leakage flux occurring between two adjacent magnets and the leakage fluxes taking place between the magnet and rotor iron at the interpolar, inner and outer edges of the magnets are considered. According to the proposed MEC and by using flux division law, some equations are extracted. A three-dimensional finite element method (FEM) is used to evaluate the proposed analytical equations. The study machine is a 3.7 kW and 1, 400 rpm TORUS-NS AFPM machine. Findings: The air gap leakage flux factor, the average air gap flux density and the flux density within the magnet are calculated using the proposed equations and FEM. All the results of FEM confirm the excellent accuracy of the proposed analytical method. Originality/value: The new equations presented in this paper can be applied for leakage flux evaluating purposes.